Blind Source separation and Echo cancellation using Discreet Wavelet transform and ICA (International Journal of Scientific Research and Management (IJSRM), 2016)
Advances in telecommunications have lead to modern technologies like conference calls, video calls, audio calls. This widely communicate over hands- free devices, where this type of communication is affected by reverberations, mixing of sources, acoustic echo etc. Goal of this paper is to estimate noise free original sources from mixture of multiple sources, and hence phenomenon known as Blind Source Separation (BSS).This implementation of source separation and estimation is performed by Independent component analysis (ICA). Aim of ICA is representing data linearly such that components must be statistically independent. De-noising was performed using discreet wavelet transform (DWT) by decomposing and thresholding. Effective results were obtained when ICADWT combinely worked than only ICA. Peak signal to noise ratio for ICA-DWT was more than only ICA.